2009
DOI: 10.1007/s11284-009-0583-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of Salix gracilistyla cuttings to a range of substrate moisture and oxygen availability

Abstract: The objective of this study is to determine the effects of substrate moisture and oxygen availability on growth traits of Salix gracilistyla Miquel, which colonizes gravel bars along rivers, the shoot growth schedule, biomass production, and resource allocation were examined under greenhouse conditions. We used four treatments representing a range of substrate moisture and oxygen availability: drought (D), flooding with standing water (FS), flooding with running water (FR), and control without drought or flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This is because under longer flooding, root biomass and root ratio are inhibited (Table 3). Root growth of S. gracilistyla cuttings is also inhibited by each hypoxic flooding or drought event (Nakai et al 2009). S. gracilistyla will not increase drought tolerance, as water absorption ability increases under conditions of longer flooding between droughts, and may suffer dehydration during the following drought.…”
Section: Discussionmentioning
confidence: 99%
“…This is because under longer flooding, root biomass and root ratio are inhibited (Table 3). Root growth of S. gracilistyla cuttings is also inhibited by each hypoxic flooding or drought event (Nakai et al 2009). S. gracilistyla will not increase drought tolerance, as water absorption ability increases under conditions of longer flooding between droughts, and may suffer dehydration during the following drought.…”
Section: Discussionmentioning
confidence: 99%
“…This is a reasonable simplification for a relative short period of growth during the vegetative growth young plants ('classical approach' for plant growth analysis, see Poorter 1989). Second, plant biomass is used as the main variable in determining flooding stress-tolerance, as it integrates all ecophysiological processes leading to growth (Nakai et al 2009;Li et al 2011), while 'stress' is defined as any environmental factor that restricts growth (sensu Grime 1989). Third, it is assumed that the use of reserve carbohydrates is essential in defining growth during (and importantly after) flooding.…”
Section: Tolerance To Flooding: Conclusion Depend On Considering Plamentioning
confidence: 99%
“…In this way, plants maximize the leaf area exposed above water, ensuring the capture of oxygen by leaves ) and facilitating root aeration (Colmer 2003). As a result of such preferential allocation of carbon to shoots-and the discontinuance of root growth-there is an increase in the shoot-to-root biomass ratio in flooded plants (Nakai et al 2009;L ie ta l .2011), which, additionally, can be seen as a reduction and an increase in the mass fraction of roots and shoots, respectively, according to Poorter et al (2012). In some cases, the magnitude of this effect can be diminished partially-but not counterbalanced-as a result of the formation porous adventitious roots (see Malik et al 2002), which help plants to alleviate the adverse effect of anaerobiosis by functionally replacing the original root system during flooding.…”
Section: Tolerance To Flooding: Conclusion Depend On Considering Plamentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2006) reported that partial flooding (intermittent) enhances root aerenchyma formation while reducing the root to shoot ratio while drought has the opposite effect in black willow. Nakai et al (2009) showed significant differences such as increased stem xylem vessel diameter and resistance to xylem cavitation with periodic water stress (flooding and drought) in various willow clones. These show a high degree of plasticity on the part of willows to respond to wide variations of water availability in their environment.…”
Section: 10mentioning
confidence: 99%